Amyloid fibrils: potential food safety implications. (9th February 2009) - Greger, Michael
The demonstration of oral Amyloid-A (AA) fibril transmissibility has raised food safety questions about the consumption of amyloidotic viscera. In a presumed prion-like mechanism, amyloid fibrils have been shown to trigger and accelerate the development of AA amyloidosis in rodent models. The finding of amyloid fibrils in edible avian and mammalian food animal tissues, combined with the inability of cooking temperatures to eliminate their amyloidogenic potential, has led to concerns that products such as pate de foie gras may activate a reactive systemic amyloidosis in susceptible consumers. Given the ability of amyloid fibrils to cross-seed the formation of chemically heterologous fibrils, the speculative etiologic role of dietary amyloid in other disease processes involving amyloid formation such as Alzheimer's disease and Type II Diabetes is also discussed.